Implementasi Pendidikan Nilai dan Karakter Dalam Pembelajaran Tematik Siswa Kelas V di SDN Renda Kabupaten Bima - Nurhayati, Nurhayati; Zainuddin, H. Mohammad; Kholidah, Lilik Nur (Jayapangus Press, 2024)
This research aims to explain the implementation of values and character education through thematic learning as well as supporting and inhibiting factors at SDN Renda, Belo District, Bima Regency. This research uses qualitative research methods with descriptive qualitative research type. Data collection uses observation, interview and documentation techniques. Observation activities carried out by researchers included the condition of school culture, gathering information about the implementation of values and character education through thematic learning, and supporting and inhibiting factors. Researchers conducted interviews with several sources who were considered to provide information related to the research focus. The documentation used is documentation that is relevant to the research topic. The process of processing and analyzing data through data collection, data reduction, data presentation, as well as conclusions and verification.